A digital measurement approach for structural condition assessment of sewers - Martins Luís Lages; Ribeiro Álvaro Silva; Almeida Maria do Céu; Brito Rita Salgado (EPJ Web of Conferences)
This paper describes the application of photogrammetric digital reconstruction within the context of structural condition assessment of sewers. The acquisition of multiple images of the observation scenario and application of the bundle adjustment technique, supported by computational algorithms dedicated to image parallel computation and clustering, is the base for the approach adopted. An orthographic camera model with uniform scaling was adopted, supported by scale coefficients determined by the relation between digital and actual (SI traceable) dimensions of reference objects visible in the generated model. The paper details experimental and computational methodologies and presents several examples of digital sewer models. Finally, an evaluation of measurement data retrieved from the models is also shown, including identifying uncertainty components related to the input quantities and their propagation by the GUM method to the output quantity, considering the mathematical models related to the adopted camera model.